2020
DOI: 10.1101/2020.07.03.186833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pex14p phosphorylation modulates import of citrate synthase 2 into peroxisomes inSaccharomyces cerevisiae

Abstract: AbstractThe peroxisomal biogenesis factor Pex14p is an essential component of the peroxisomal matrix protein import machinery. Together with Pex13p and Pex17p, it is part of the membrane-associated peroxisomal docking complex in yeast, facilitating the binding of cargo-loaded receptor proteins for translocation of cargo proteins into the peroxisome. Furthermore, Pex14p is part of peroxisomal import pores. The central role of Pex14p in peroxisomal matrix protein import processes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 89 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…These phosphatases are conserved among eukaryotes and a peroxisomal localization was reported for the protein from Arabidopsis thaliana (Kataya et al, 2019, Lillo et al, 2014). Recently, regulation of peroxisomal matrix protein import via phosphorylation of Pex14p, a key component of the import machinery, was reported, is may be that yeast Tpd3p in involved in this process (Schummer et al, 2020). Shr5p (Erf4) is involved in the palmitoylation and subcellular localization of yeast Ras protein (Zhao et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…These phosphatases are conserved among eukaryotes and a peroxisomal localization was reported for the protein from Arabidopsis thaliana (Kataya et al, 2019, Lillo et al, 2014). Recently, regulation of peroxisomal matrix protein import via phosphorylation of Pex14p, a key component of the import machinery, was reported, is may be that yeast Tpd3p in involved in this process (Schummer et al, 2020). Shr5p (Erf4) is involved in the palmitoylation and subcellular localization of yeast Ras protein (Zhao et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…This binding site appears to be required for the import of oligomeric PTS1 cargos as shown by the loss of import of tetrameric catalase 101 . Finally, DTM phosphorylation may also have an important role as it has been shown that specific Pex14 phosphorylation sites may affect interactions between DTM components, which could also affect the Pex5 export and subsequent recycling process 102‐104 . The function of these phosphorylation sites remains to be determined, and thus far only defects in the import of certain cargos (catalase, citrate synthase 2) under specific conditions such as mitosis and oxidative stress have been detected, rather than a more general effect on cargo import 103,104 …”
Section: Possible Roles Of Allostery In Pex5 Receptor Cargo Translocamentioning
confidence: 99%
“…The talk by Renate Maier (Bettina Warscheid laboratory, University of Freiburg, Germany) addressed the question if phosphorylation of Pex14p plays a role in regulating peroxisomal matrix protein import. They established a comprehensive Pex14p in vivo phosphorylation map of Saccharomyces cerevisiae using high-resolution mass spectrometry (Schummer et al 2020 ). Their analysis of single phosphomimicking and non-phosphorylatable Pex14p variants revealed that a phosphomimetic mutation of Pex14p at serine 266 results in impaired growth and reduced peroxisomal import of citrate synthase 2 (Cit2p).…”
Section: Session 5: Chair: Vishal Kalel Ruhr-university Bochum Germanymentioning
confidence: 99%